The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fimmu.2023.1266315
|View full text |Cite
|
Sign up to set email alerts
|

Takinib inhibits microglial M1 polarization and oxidative damage after subarachnoid hemorrhage by targeting TAK1-dependent NLRP3 inflammasome signaling pathway

Weihan Wang,
Cong Pang,
Jiaxing Zhang
et al.

Abstract: Transforming growth factor-β-activated kinase 1 (TAK1) positively regulates oxidative stress and inflammation in different diseases. Takinib, a novel and specific TAK1 inhibitor, has beneficial effects in a variety of disorders. However, the effects of takinib on early brain injury (EBI) after subarachnoid hemorrhage (SAH) and the underlying molecular mechanisms remain unknown. Our study showed that takinib administration significantly inhibited phosphorylated TAK1 expression after SAH. In addition, takinib su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Neuroinflammation plays a pivotal role in the pathogenesis of EBI subsequent to SAH [ 38 ]. Shortly after the occurrence of SAH, neuroinflammation promptly ensues, characterized by glial cell activation and the release of pro-inflammatory cytokines, matrix metalloproteinases, cytotoxic factors, and more [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation plays a pivotal role in the pathogenesis of EBI subsequent to SAH [ 38 ]. Shortly after the occurrence of SAH, neuroinflammation promptly ensues, characterized by glial cell activation and the release of pro-inflammatory cytokines, matrix metalloproteinases, cytotoxic factors, and more [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B inhibitor (PTP1B-in-1) can regulate the IRS-2/AKT signaling pathway, improve neuroinflammation and neuronal apoptosis, and exert neuroprotective functions [ 73 ]. In animal experiments, it was found that takinib alleviates EBI by targeting the inhibition of the TAK1-ROS-NLRP3 inflammasome signaling pathway [ 74 ]. Inhibiting miR-26b can alleviate EBI by mediating the upregulation of KLF4/downregulation of STAT3/downregulation of HMGB1 signaling pathways [ 75 ].…”
Section: Potential Mechanisms Of Early Brain Injurymentioning
confidence: 99%
“…TAK1 mediates the production of ROS, exacerbating oxidative damage in different disease models ( 16 , 17 ). In the central nervous system (CNS), TAK1 is mainly expressed in neurons, where it modulates a variety of intracellular signaling pathways ( 18 ). It has demonstrated that TAK1 blockade restrains phosphorylated NF-κB p65 expression and NLRP3 inflammasome activation post-subarachnoid hemorrhage (SAH) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%